DiaActive protocol: A randomized controlled trial of cognitive‐motor multicomponent exercise to reduce fall rate in older adults with diabetes - Aksayan Arunanthy Mahalingasivam; Asger Ahlmann Bech; Peter Vestergaard; Martin Grønbech Jørgensen; Nicklas Højgaard‐Hessellund Rasmussen (Diabetic Medicine, 2026)
Abstract Introduction Older adults with diabetes have an increased risk of falls due to neuropathy, impaired bone health and cardiovascular disease, resulting in significant morbidity and mortality. Conventional fall‐prevention programmes primarily target strength and balance, while cognitive‐motor integration, essential for safe mobility in complex environments, is often overlooked. Multicomponent exercise combining physical and cognitive training may therefore provide additional benefits in this population. Methods The DiaActive trial is a single‐centre, stratified, parallel‐group randomized controlled trial including adults aged ≥65 years with type 1 or type 2 diabetes. After comprehensive baseline assessments, 440 participants (220 with type 1 diabetes and 220 with type 2 diabetes) with low‐to‐moderate fall risk are randomized 1:1 within diabetes type to a 26‐week cognitive‐motor multicomponent exercise intervention (RYMA) or usual care. The intervention includes two weekly supervised sessions combining rhythm‐based motor training with activities‐of‐daily‐living–focused strength and balance exercises. Results The primary outcome is fall rate during the intervention, assessed using weekly fall calendars. Secondary outcomes include balance performance, fall‐related outcomes, bone mineral density, fractures, neuropathy progression, cardiovascular risk markers, muscle strength and cognitive function. Follow‐up continues to 104 weeks, with registry‐based outcomes assessed at 5 years. Conclusion The trial is approved by the North Denmark Region Ethics Committee (N‐20240025). Written informed consent will be obtained. Results will be disseminated through peer‐reviewed publications, conferences and stakeholder engagement.